At the Gate of Mutualism: Identification of Genomic Traits Predisposing to Insect-Bacterial Symbiosis in Pathogenic Strains of the Aphid Symbiont Serratia symbiotica - Renoz, François; Foray, Vincent; Ambroise, Jérôme; Baa-Puyoulet, Patrice; Bearzatto, Bertrand; Mendez, Gipsi Lima; Grigorescu, Alina S.; Mahillon, Jacques; Mardulyn, Patrick; Gala, Jean-Luc; Calevro, Federica; Hance, Thierry (Frontiers in Cellular and Infection Microbiology, 2021)
Mutualistic associations between insects and heritable bacterial symbionts are ubiquitous in nature. The aphid symbiont Serratia symbiotica is a valuable candidate for studying the evolution of bacterial symbiosis in insects because it includes a wide diversity of strains that reflect the diverse relationships in which bacteria can be engaged with insects, from pathogenic interactions to obligate intracellular mutualism. The recent discovery of culturable strains, which are hypothesized to resemble the ancestors of intracellular strains, provide an opportunity to study the mechanisms underlying bacterial symbiosis in its early stages. In this study, we analyzed the genomes of three of these culturable strains that are pathogenic to aphid hosts, and performed comparative genomic analyses including mutualistic host-dependent strains. All three genomes are larger than those of the host-restricted S. symbiotica strains described so far, and show significant enrichment in pseudogenes and mobile elements, suggesting that these three pathogenic strains are in the early stages of the adaptation to their host. Compared to their intracellular mutualistic relatives, the three strains harbor a greater diversity of genes coding for virulence factors and metabolic pathways, suggesting that they are likely adapted to infect new hosts and are a potential source of metabolic innovation for insects. The presence in their genomes of secondary metabolism gene clusters associated with the production of antimicrobial compounds and phytotoxins supports the hypothesis that S. symbiotia symbionts evolved from plant-associated strains and that plants may serve as intermediate hosts. Mutualistic associations between insects and bacteria are the result of independent transitions to endosymbiosis initiated by the acquisition of environmental progenitors. In this context, the genomes of free-living S. symbiotica strains provide a rare opportunity to study the inventory of genes held by bacterial associates of insects that are at the gateway to a host-dependent lifestyle.